Integrative structure of a 10-megadalton eukaryotic pyruvate dehydrogenase complex from native cell extracts - Kyrilis, Fotis L.; Semchonok, Dmitry A.; Skalidis, Ioannis; Tüting, Christian; Hamdi, Farzad; O’Reilly, Francis J.; Rappsilber, Juri; Kastritis, Panagiotis L. (Cell reports (Cambridge), 2021)
The pyruvate dehydrogenase complex (PDHc) is a giant enzymatic assembly involved in pyruvate oxidation. PDHc components have been characterized in isolation, but the complex’s quaternary structure has remained elusive due to sheer size, heterogeneity, and plasticity. Here, we identify fully assembled Chaetomium thermophilum α-keto acid dehydrogenase complexes in native cell extracts and characterize their domain arrangements utilizing mass spectrometry, activity assays, crosslinking, electron microscopy (EM), and computational modeling. We report the cryo-EM structure of the PDHc core and observe unique features of the previously unknown native state. The asymmetric reconstruction of the 10-MDa PDHc resolves spatial proximity of its components, agrees with stoichiometric data (60 E2p:12 E3BP:∼20 E1p: ≤ 12 E3), and proposes a minimum reaction path among component enzymes. The PDHc shows the presence of a dynamic pyruvate oxidation compartment, organized by core and peripheral protein species. Our data provide a framework for further understanding PDHc and α-keto acid dehydrogenase complex structure and function. [Display omitted] •2-oxo-acid dehydrogenase complexes are studied by integrative analysis of cell extracts•A cryo-EM structure of the active, native pyruvate dehydrogenase complex is resolved•Asymmetric cryo-EM maps reveal enzyme clustering during pyruvate oxidation•A transiently formed catalytic chamber is defined as the “pyruvate dehydrogenase factory” Kyrilis et al. combine diverse biochemical and biophysical methods to probe native cell extract organization. They report an asymmetric reconstruction of the active, native pyruvate dehydrogenase complex by cryo-EM and determine the spatial relationships among the protein components in the dynamic assembly. They identify enzyme clusters that form a transient catalytic nanocompartment and define this as the “pyruvate dehydrogenase factory.”